School Literacy Movement Enhancing Students' Writing Skills and Creative Thinking Skills - Wayan Arini; I Ketut Dibia; I Gede Wira Bayu (Universitas Pendidikan Ganesha, 2020)
The low of students' writing skills due to the lack of knowledge of students in writing. In addition, teachers also experience difficulties in fostering student creativity in writing. This study aims to analyze the effectiveness of the school literacy movement to improve writing skills and creative thinking skills in students. The subjects of this study were 24 students. The object of this research is the students' writing skills and creative thinking skills after the implementation of the school literacy movement. This research was conducted in several cycles. Each cycle consists of four stages, namely: Planning, Implementing Action, Observation and Evaluation of Actions, and Reflection. The data collection method used in this study is the test method. Methods of data analysis using quantitative descriptive statistical analysis methods. Based on the calculation results, the average writing skills of students in the first cycle was 67.67, increasing to 78.67 in the second cycle. While the creative thinking ability of students in the first cycle was 63.33, increasing to 75.10 in the second cycle. The improvement of students' writing skills and creative thinking abilities from cycle I to cycle II was in the medium category. It can be concluded that the school literacy movement can effectively improve students' writing skills and creative thinking skills.